Efficacy of PD-(L)1 inhibitors plus anlotinib in the second-line treatment of extensive-stage small cell lung cancer - Jian Zhang; Zijie Wu; Shuyun Wang; Yanxin Sun; Jiake Wu; Dahai Wang; Yihui Ge; Juan Li; Haifeng Sun; Qinglei Cheng; Aiqin Gao; Yuping Sun (BMC Cancer)
Abstract Background The efficacy of second-line therapy for extensive-stage small cell lung cancer (ES-SCLC) is still limited, with the PFS of 2–3 months. Given the synergistic effect of PD-(L)1 inhibitors and anti-angiogenic agents, their combination represents a novel and promising strategy to reprogram the protumoral microenvironment and improve patient outcome. However, the efficacy of PD-(L)1 inhibitors plus anlotinib as the second-line treatment of ES-SCLC is undetermined in the real world. Methods We retrospectively analyzed 389 ES-SCLC patients from 3 cancer centers. All the patients received one of the following second-line schemes: PD-(L)1 inhibitors plus anlotinib (I + A), PD-(L)1 inhibitors plus chemotherapy (I + C), or chemotherapy alone (C). The efficacy, including the objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), overall survival (OS), and safety were compared among the three groups. We also analyzed the impact of first-line immune checkpoint inhibitors (ICIs) on the efficacy of second-line I + A. Results The baseline clinical characteristics among three groups were largely balanced. I + A treatment demonstrated significantly higher ORR (30.2%) and DCR (82.6%) compared with I + C (ORR = 17.6%, DCR = 68.8%) and C (ORR = 18.0%, DCR = 53.9%). Furthermore, I + A group showed the longest mPFS (7.2 months) and mOS (33.5 months), compared to I + C (mPFS = 4.6 months, mOS = 19.0 months, both P < 0.001) and C (mPFS = 3.4 months, P < 0.01; mOS = 18.3 months, P = 0.083). The benefit of I + A treatment persists independent of the administration of first-line ICIs. A stratified analysis revealed that female patients and those with oligometastasis (≤ 3 metastatic sites) benefit more from I + A treatment than male patients and those with polymetastasis. In terms of safety, I + A group displayed the lowest incidence of ≥ grade 3 myelosuppression compared to the I + C and C groups (3.5% vs. 11.2% vs. 16.3%, P < 0.01). However, I + A treatment was associated with a higher prevalence of immune-related pneumonia (2.3% vs. 0% vs. 0%, P < 0.05) and hemoptysis (1.4% vs. 0% vs. 0.6%, P < 0.05) compared to I + C and C treatment. Conclusions PD-(L)1 inhibitors and anlotinib has promising efficacy and manageable toxicity as the second-line therapy of ES-SCLC.